Analysis of strain conditions baseplates on ground subsiding seismic response - V Ivanovich Obozov; M Anatol'evich Tolstoyh (RUDN Journal of Engineering Research, 2010)
The article presents the research results of calculation base plate frame buildings under seismic effects of subsidence in the soil. The estimation of the influence of wetted soil subsidence on the stress-strain state of a base plate.